p62/SQSTM1 accumulation in squamous cell carcinoma of head and neck predicts sensitivity to phosphatidylinositol 3-kinase pathway inhibitors. - Wen-Liang Kuo; Marina N Sharifi; Mark W Lingen; Omar Ahmed; Jing Liu; Madhavi Nagilla; Kay F Macleod; Ezra E W Cohen (PLoS ONE)
The phosphoinositol-3 kinase (PI3K) pathway is highly dysregulated in squamous cell carcinoma of the head and neck (SCCHN). While inhibitors of the PI3K/AKT pathway are being developed in cancer, their efficacy does not appear to be related to the presence of mutations or amplification in pathway genes. The PI3K pathway is a major regulator of macro-autophagy, an evolutionarily conserved catabolic process that degrades cellular materials to promote cellular homeostasis and survival under stress. Employing a panel of SCCHN cell lines, we observed a significant correlation between the activity of PI3K/AKT inhibitors and their ability to induce autophagy. More specifically, resistance to these inhibitors was associated with accumulation of p62/SQSTM1, a pleotropic protein that is consumed during autophagy, while loss of autophagy was, for the first time, found to be due to silencing of an essential autophagy gene, ATG7. Moreover, modulating ATG7 and p62/SQSTM1 could regulate sensitivity to PI3K/AKT inhibitors, underscoring a mechanistic link between autophagy and drug sensitivity. Analysis of human tissues revealed progressive accumulation of p62/SQSTM1 in a significant proportion of cancer samples compared to normal tissue, suggesting that defective autophagy has relevance to SCCHN. These findings are further validated by analysis of TCGA data confirming homozygous deletion and mRNA down-regulation of ATG7 in 10.0% of SCCHN samples. Taken together, these data indicate that p62/SQSTM1 levels modulate sensitivity to PI3K/AKT inhibitors; cancers vary in their capacity to undergo autophagy through epigenetic modification and, when deficient, accumulate p62/SQSTM1; and expression of autophagy-related proteins may serve as markers for resistance to PI3K/AKT inhibitors in SCCHN.